SAFETY MANAGEMENT IN CONSTRUCTION PROJECTS - SAEED, YOUSIF S. (Journal of Duhok University, 2017)
The aim of this research is to identify and evaluate the safety management in construction projects to minimise and control health and safety (H&S) of construction workers. Questionnaire is used to collected a wide range of opinions from experienced professionals working in different construction sites for comparison between them. The reviews of the related literature are the first step in obtaining information from previously related studies. The literature reviews provide a theoretical background about safety management that guided the design of the questionnaire. This research concludes that the construction industry has a high number of fatalities and long-term injuries. This is unacceptable in a modern society and it also makes the industry inefficient, with days lost due to injuries. This research shows that the high rates of accidents are due to several common factors, such as poor construction planning, lack of safety in design, inadequate safety training, worker behaviour, inherent safety H&S risk of construction and lack of knowledge of site rules.